2019
DOI: 10.1002/pd.5580
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early diagnosis and noninvasive prenatal testing (NIPT): Knowledge, attitudes, and experiences of parents of children with sex chromosome aneuploidies (SCAs)

Abstract: Objective To investigate the attitudes of parents of children with a sex chromosome aneuploidy (SCA) regarding the impact of an early diagnosis and noninvasive prenatal testing (NIPT). Method A survey consisting of multiple choice and long response formatted questions was completed by parents of children with SCA(s). Results Fifty‐five participants responded to the survey. A total of 88.1% of participants who received an early diagnosis expressed that it had a positive impact on their child's life. Of the 23 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 54 publications
0
38
0
Order By: Relevance
“…Recent studies demonstrated that early interventions such as postnatal hormone therapy, physical therapy and occupational therapy can have positive in uences on the behavioral phenotype or neurodevelopmental outcomes if applied earlier to SCA patients [11] . Prenatal screening and diagnosis of SCA can provide the opportunity for early intervention, postnatal comprehensive management and improve the quality of life of the affected child [12,26,27,28] . Sex chromosome abnormalities are more common than the major trisomies at birth and the neonates are often phenotypically normal [30] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies demonstrated that early interventions such as postnatal hormone therapy, physical therapy and occupational therapy can have positive in uences on the behavioral phenotype or neurodevelopmental outcomes if applied earlier to SCA patients [11] . Prenatal screening and diagnosis of SCA can provide the opportunity for early intervention, postnatal comprehensive management and improve the quality of life of the affected child [12,26,27,28] . Sex chromosome abnormalities are more common than the major trisomies at birth and the neonates are often phenotypically normal [30] .…”
Section: Discussionmentioning
confidence: 99%
“…SCAs refer to conditions caused by numerical abnormalities in X and Y chromosomes, including Turner syndrome (45,X), triple X syndrome (47,XXX), Klinefelter syndrome (47,XXY) and 47,XYY syndrome (47,XYY) [1] . In general, SCA are usually experienced with infertility, short or tall stature, behavioral problems, mental disorder and developmental delay in intelligence and sexual [1,12] . However, the phenotype of patients span a large range of associated symptoms that vary in severity depending on the timing of diagnosis and types of SCA [6,7,8,9,10,11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that early interventions such as postnatal hormone therapy, physical therapy, and occupational therapy could have positive effects on the behavioral phenotype or neurodevelopmental outcomes if applied earlier to SCA patients [9,29] . Prenatal screening and diagnosis of SCA can provide the opportunity for early intervention, comprehensive postnatal management, and improve the quality of life of the affected child [10] . Sex chromosome abnormalities are more common than the major trisomies at birth, and the neonates are often phenotypically normal [30] .…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of SCA is estimated to be 1 in every 500 live births. About 75-90% of cases are undiagnosed during their lifetime [10] . Recently, studies reported that postnatal hormone therapy could have positive effects on behavioral phenotype if applied earlier to SCA patients.…”
Section: Introductionmentioning
confidence: 99%